Red gram hybrids in India: A 40-year journey of research - Choudhary, A K; Kumar, R V; Saxena, K B (Indian Farming, 2015)
The results and empirical evidences have shown beyond doubt that CMS-based pigeonpea hybrids are indeed capable of making a positive change in the productivity of pigeonpea. Available literature and reports reveal that some experimental hybrids have shown superiority over the best check by even more than 100%, yielding more than 4500 kg/ha in absolute terms. It is now evident that the three line (A, B and R line) system of hybrid breeding can be exploited at commercial level in pigeonpea. However, this hybrid technology is still in infancy. It needs further refinement and perfection. Parents of the hybrid need to be improved for yield and other desirable traits. Such improved parents are likely to produce higher yielding hybrids than the present ones. For commercialization and wide adoption of the hybrids, publicprivate partnership/linkage will have to be established. Some private seed companies have already initiated hybrid breeding programmes. Such linkages are expected to have greater impact for wide adoption of hybrids by the farmers, making hybrid technology in pigeonpea a ground reality.